Determinasi Kebijakan Dividen: Peran Stabilitas Pendapatan dan Kebijakan Utang pada Perusahaan Properti di Indonesia - Azlim, Azlim; Pramida, Lili; Agusmadi; Marzuki (Universitas Muria Kudus, 2026)
This study aims to analyze the effect of income stability and debt policy on dividend policy in property and real estate companies listed on the Indonesia Stock Exchange. The study uses a quantitative approach, using secondary data from companies' annual financial reports during the observation period. The analysis method used is multiple linear regression, with classical assumption testing for normality, multicollinearity, and heteroscedasticity to ensure the validity of the regression model. The results show that income stability has a positive and significant effect on dividend policy, indicating that companies with more stable income tend to have greater ability and confidence in distributing dividends to shareholders. Conversely, debt policy has a negative, significant effect on dividend policy, meaning that the higher the debt level, the lower the tendency for companies to distribute dividends due to increased financial obligations. Simultaneously, income stability and debt policy have a significant effect on dividend policy. The findings of this study have implications for corporate management in formulating optimal dividend policies that take into account income stability and funding structure. In addition, the results of this study can be considered by investors when making investment decisions.